El misterio de la maldicion de la mala suerte - Williams, Laura E. (New York : Scholastic, 2005)
Many years ago a terrible crime was committed in Mystic, Maine. The ghost of the criminal is said to haunt the area and that anyone who disturbs the scene of the crime will be struck with a bad luck curse. When archaeologists try to figure out what happened strange things occur. Jen and Zeke must uncover the secrets of the old legend before the curse turns deadly.
New December 2006.
Spanish language collection.
Keywords: Buried treasure -- Juvenile fiction; Caribbean Area -- Juvenile fiction; Mystery and detective stories; Shipwrecks -- Caribbean Area -- Juvenile fiction; Spanish language materials -- Juvenile fiction